A method for recovering copper matte nickel material to prepare copper powder, nickel sulfide and iron phosphate
Through steps such as roasting, crushing and multi-stage leaching, the physical and chemical properties of copper sulfonium nickel materials are improved, and the complexity and high cost problems of high copper sulfonium nickel materials are solved in the prior art are solved, thereby achieving efficient and low-cost metal recycling and closed-loop utilization of resources.
Patent Information
- Application Number
- CN202510020990.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-04
AI Technical Summary
The existing hydrometallurgical technology has problems such as complex process, low leaching efficiency, large energy consumption and high production costs when dealing with high copper nickel materials, and it is difficult to effectively recover precious metals.
The steps of calcining, crushing, three-stage leaching, replacement copper depositing, ammonium method synthesis of iron phosphate, nickel sulfide precipitation and regenerated ammonium dihydrogen phosphate are improved by improving the physical and chemical properties of copper nickel material, and the leaching and recovery rate of metals are improved.
It realizes low-cost and high-efficiency metal recycling, improves the recovery rate of copper, nickel and iron, reduces production costs, and realizes effective recycling of precious metals and closed-loop reuse of resources.
Smart Images

Figure CN119753319A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nonferrous metal hydrometallurgy and comprehensive resource utilization, and in particular to a method for recovering copper matte nickel material to prepare copper powder, nickel sulfide and iron phosphate. Background Art
[0002] In the existing metal recovery technology, the treatment of high-copper matte nickel materials mainly adopts two methods: pyrometallurgy and hydrometallurgy. Pyrometallurgy usually includes smelting and blowing processes. High-copper matte nickel materials are smelted at high temperatures to separate copper, nickel and other metals, and then further oxidized and blown to improve the purity of the metal. This method has high energy consumption, low metal recovery rate, and is prone to produce harmful gases and dust, causing environmental pollution. Hydrometallurgy involves steps such as leaching, solvent extraction, and electrolysis. High-copper matte nickel materials are leached through acidic or alkaline solutions to dissolve the metals. The metals in the leachate are extracted and separated by organic solvents, and then reduced and deposited as metals in the electrolytic cell. However, traditional hydrometallurgy has problems such as complex process, low leaching efficiency, high extraction cost, and high energy consumption in the electrolysis process. In addition, the chemical properties of high-copper matte nickel materials are complex and contain a variety of chemical elements, such as nickel, copper, iron, sulfur and precious metals. These elements have different chemical properties and react with leaching agents. The high requirements for properties and selectivity make the leaching process more complicated. At the same time, the physical properties of high-copper matte nickel materials, such as particle size, porosity, etc., will also affect the contact area and reaction rate between the leachate and the material, thereby affecting the leaching efficiency. In addition, the complex "three wastes" treatment process and limited reaction conditions will increase the difficulty, process complexity and production cost of leaching high-copper matte nickel materials. Therefore, how to provide a low-cost, high-leaching efficiency hydrometallurgical separation of copper, nickel and iron process technology has become a technical problem that people in this field need to solve urgently. Summary of the invention
[0003] The present invention aims to provide a method for recycling copper matte nickel material to prepare copper powder, nickel sulfide and ferric phosphate, so as to reduce production costs, improve leaching efficiency, and further improve metal recovery efficiency and realize closed-loop reuse of resources.
[0004] To achieve the above object, the present invention provides the following technical solutions: A method for recovering copper matte nickel material to prepare copper powder, nickel sulfide and iron phosphate comprises the following steps: S1, roasting: after uniformly mixing the copper matte nickel material and soda ash in a mass percentage of 1:0.03-0.05, place in a roasting equipment and roast at 800-850° C. for 1.5-3 hours to obtain a roasted material; S2, crushing: placing the calcined material obtained in step 1 in a grinding device and crushing it to 80-120 mesh to obtain copper matte nickel powder; S3, three-stage leaching: the copper matte nickel powder obtained in step S2 is added to the leaching solution at a solid-liquid ratio of 1:5-6, and a first-stage soda ash and sulfuric acid double leaching reaction is carried out. The leaching solution is a mixed solution of sodium chlorate and soda ash, the mass percentage of the sodium chlorate to the copper matte nickel material is 1:32-35, and the soda ash concentration is 10-12g / L. After the first-stage soda ash and sulfuric acid double leaching reaction is completed, a first-stage leaching solution and a first-stage leaching residue are obtained after filtration. The first-stage leaching residue is subjected to a second-stage sulfuric acid leaching reaction, and a second-stage leaching solution and a second-stage leaching residue are obtained after filtration. The second-stage leaching solution can be added to the leaching solution for repeated recycling. The second-stage leaching residue is subjected to a third-stage sulfuric acid leaching reaction, and a third-stage leaching solution and a third-stage leaching residue rich in precious metals of gold, silver, platinum are obtained after filtration. The third-stage leaching solution can be added to the second-stage sulfuric acid leaching reaction; S4, copper replacement precipitation: detect the content of copper, nickel and iron in the first leaching solution in step S3, add a replacement agent to the first leaching solution according to the mass ratio of replacement agent: copper = 1.2-1.4 to carry out replacement reaction for 20-30 minutes, control the temperature at 40-50°C, obtain a copper filter cake and a first filtrate after filtering, and obtain copper powder after the copper filter cake is dried; S5, ammonium method synthesis of iron phosphate: the first filtrate obtained in step S4 is first heated to 70-80°C, and hydrogen peroxide and ammonium dihydrogen phosphate are slowly added simultaneously, wherein the amount of hydrogen peroxide added is 2.1-2.5% of the mass of the first filtrate, and the concentration of ammonium dihydrogen phosphate is 40-45 g / L, and phosphoric acid is added to control the end point pH to 1.6-1.8. After detecting that the divalent iron ions are completely converted into trivalent iron ions, the temperature is continued to be raised to 90-95°C, kept warm for 2-3 hours, aged for 3-4 hours, and dihydrate iron phosphate slurry is obtained. After filtering and separation, an iron phosphate filter cake and a second filtrate are obtained. The iron phosphate filter cake is washed, dried at 140-160°C for 2-3 hours, and calcined at 650-700°C for 3-4 hours to obtain battery-grade iron phosphate; S6, sulfidation and nickel precipitation: sodium sulfide is added to the second filtrate obtained in step S5, the mass ratio of sodium sulfide to nickel content in the second filtrate is 11-13:1, the sulfidation reaction is carried out for 30-40 minutes, the temperature is controlled at 40-50°C, and a nickel sulfide filter cake and a third filtrate are obtained after filtration, and the nickel sulfide filter cake is dried to obtain nickel sulfide; S7, regeneration of diammonium phosphate: add calcium dihydrogen phosphate at 12-15 g / L to the third filtrate obtained in step S5, control the temperature at 55-65° C., regenerate for 30-40 minutes, then add ammonia water to adjust the pH value to 4.5-5.0, and continue to react for 50-60 minutes, and obtain calcium sulfate gypsum slag and diammonium phosphate liquid after filtration. The diammonium phosphate is finely filtered again and then reused in step S5 to synthesize iron phosphate.
[0005] Furthermore, the copper matte nickel material in step S1 contains but is not limited to the following chemical elements: copper, nickel, iron, sulfur, silver, and platinum. The mass percentage of the copper matte nickel material to soda ash is 1:0.04. The roasting equipment adopts a muffle furnace, and the roasting time is 2 hours.
[0006] Furthermore, the grinding equipment in step S2 is a ball mill, and the calcined material is crushed into a particle size of 100 meshes.
[0007] Further, the mass percentage of sodium chlorate and copper-matt nickel material in the leaching solution of step S3 is 1: 33, the concentration of soda ash is 12g / L, the solid-liquid ratio of copper matte nickel powder to leaching solution is 1:5, the first stage soda ash and sulfuric acid double leaching reaction is to place the copper matte nickel powder in the leaching solution and stir evenly, control the temperature to 70℃-75℃ for alkaline leaching reaction for 30 minutes, then slowly add concentrated sulfuric acid, add sodium chlorate in an amount equal to that of alkaline leaching to continue acid leaching reaction for 60 minutes, and control the pH to 1.5-2.0, the second stage sulfuric acid leaching reaction is to place the first stage leaching residue in 5% sodium chlorate solution and stir evenly, slowly add concentrated sulfuric acid, acid leaching reaction for 90 minutes, control the temperature to 70℃, control the pH to 1.5-2.0, and add sodium chlorate during the period, the third stage sulfuric acid leaching reaction is to place the second stage leaching residue in 5% sodium chlorate solution and stir evenly, slowly add concentrated sulfuric acid, acid leaching reaction for 90 minutes, control the temperature to 70℃, control the pH to 1.5-2.0, and add sodium chlorate during the period.
[0008] Furthermore, in step S4, the mass ratio of the replacement agent to copper is 1:1.3, and the replacement agent is iron powder.
[0009] Furthermore, in step S5, the amount of hydrogen peroxide added is 2.4% of the mass of the first filtrate, and the concentration of diammonium phosphate is 45 g / L.
[0010] Furthermore, in step S6, the mass ratio of the sodium sulfide to the nickel content in the second filtrate is 12:1.
[0011] Furthermore, in step S7, calcium dihydrogen phosphate is added to the third filtrate at 14 g / L.
[0012] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention achieves effective recovery of these metals and converts them into related products, such as copper powder, nickel sulfide, and iron phosphate, by the steps of roasting, crushing, three-stage leaching of copper-nickel-iron, replacement copper precipitation, ammonium method synthesis of iron phosphate, nickel sulfide precipitation, and regeneration of ammonium dihydrogen phosphate, thereby harmlessly treating and recycling valuable metal ions, and reducing production costs. The present invention has a simple process and is easy to operate. It is an efficient hydrometallurgical separation process for separating copper matte nickel materials to prepare copper powder, nickel sulfide, and iron phosphate, and has the advantages of low cost and short process.
[0013] 2. By adding alkali to activate the calcination, the high-sulfur copper-nickel material that is difficult to dissolve and leach is transformed into a crystal phase and its pore structure is improved, thereby increasing the leaching rate of different metals in the material during the leaching stage. This process not only improves the pore size distribution of the material, but also changes the difficult-to-leach crystal phase, making metal ions easier to dissolve and extract.
[0014] 3. Through multiple leaching and subsequent treatment steps, closed-loop resource reuse is achieved. The second-stage leaching solution can be added to the leaching solution for repeated recycling, the third-stage leaching solution can be added to the second-stage sulfuric acid leaching reaction, and the diammonium phosphate solution is finely filtered again and reused to synthesize iron phosphate, which not only improves resource utilization and realizes sustainable resource utilization, but also reduces waste emissions and environmental pollution, achieving a triple improvement in resource, economic and environmental benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION
[0016] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0017] An embodiment provided by the present invention is a method for recovering copper matte nickel material to prepare copper powder, nickel sulfide and iron phosphate, the process flow is as follows: Figure 1 As shown, the following steps are included: S1. Calcination: After uniformly mixing copper matte nickel material and soda ash in a mass percentage of 1:0.04, the mixture is placed in a muffle furnace and calcined at 800-850° C. for 2 hours to obtain a calcined material.
[0018] The copper matte nickel material contains copper, nickel, iron, sulfur, silver, platinum, and other chemical elements. The copper matte nickel material used in the present invention has a composition of copper 25%-35%, nickel 15%-20%, iron 8%-12%, sulfur 2%-5%, silver 70g / t-100g / t, gold 3g / t-5g / t, and platinum 3g / t-8g / t. During the roasting process, soda ash (i.e., sodium carbonate Na2CO3) reacts with copper, nickel, and iron sulfides in the copper matte nickel material to promote the difficult-to-dissolve and difficult-to-leach copper matte. The nickel material undergoes a crystal phase transformation to generate metal oxides (copper oxide, nickel oxide, ferric oxide) and sulfates that are easier to leach, thereby increasing the leaching rate of metals in the subsequent leaching process. In addition, during the high-temperature roasting process, volatile substances (such as sulfur) in the copper matte nickel material will escape to form holes, thereby improving the pore structure and pore size distribution of the copper matte nickel material, which helps to increase the specific surface area of the copper matte nickel material, making it easier for the leaching solution to penetrate into the material, further improving the leaching efficiency of the metal. Precious metals such as gold, silver, and platinum in the copper matte nickel material form fine particles at high temperatures, and some of them gather on the surface of the material or in the pores, which is conducive to the subsequent enrichment and recovery of precious metals in the leaching slag. High-temperature roasting also helps to remove harmful impurities in the copper matte nickel material, such as organic matter and chloride ions, and reduce side reactions and corrosion problems in the subsequent hydrometallurgical process.
[0019] The physical and chemical properties of copper-nickel matte materials treated with soda ash and high-temperature roasting are improved, which is beneficial to the stability and selectivity of subsequent leaching and separation processes, improves the leaching efficiency and recovery rate of metals, and reduces energy consumption and production costs. This is of great significance for achieving low-cost and high-efficiency comprehensive recovery of copper-nickel matte materials.
[0020] S2, crushing: the calcined material obtained in step 1 is placed in a ball mill and crushed to 100 mesh to obtain copper matte nickel powder.
[0021] The copper-nickel matte material after crushing has a smaller particle size and a larger specific surface area, which helps to increase the contact area between the leachate and the target metal in the copper-nickel matte material in the subsequent leaching process and improve the leaching efficiency. The crushing process helps to obtain a uniform particle size, ensuring consistency and predictability in the processing process. Crushing can also reduce the agglomeration of material particles, which will hinder the contact between the leachate and the copper-nickel matte particles and reduce the leaching efficiency. Smaller particle size can speed up the leaching reaction rate, because smaller particles mean a shorter diffusion distance, and metal ions can migrate faster from the inside of the copper-nickel matte material to the leachate.
[0022] S3, three-stage leaching: the copper matte nickel powder obtained in step S2 is added to the leaching solution at a solid-liquid ratio of 1:5, and a double leaching reaction of soda ash and sulfuric acid is carried out. The leaching solution is a mixed solution of sodium chlorate and soda ash. The mass percentage of sodium chlorate to copper matte nickel material is 1:33, the concentration of soda ash is 12g / L, the solid-liquid ratio is 1:5 and the composition and content of the leaching solution are determined according to experiments to achieve the best leaching effect. The first stage of soda ash and sulfuric acid double leaching reaction is to place the copper matte nickel powder in the leaching solution and stir it evenly, control the temperature to 70℃ for alkaline leaching reaction for 30 minutes, and then slowly add concentrated sulfuric acid to change the solution from an alkaline environment to an acidic environment, which is conducive to the dissolution of metal sulfides and improve the leaching rate of metals. Sodium chlorate is added in an amount equal to that of alkaline leaching to continue the acid leaching reaction for 60 minutes, and the pH is controlled at 2.0. In the alkaline leaching reaction, the soda ash hydrolyzes to generate NaOH, which increases the concentration of hydroxide ions in the solution and is used to maintain the alkaline environment during the leaching process, which is conducive to the dissolution of copper, nickel and iron in the copper matte nickel powder, and can also destroy the structure of the copper matte nickel powder, making the metal easier to be extracted in the subsequent acid leaching. Sodium chlorate can more effectively extract Metal sulfides are converted into soluble metal hydroxides, which make it easier to leach from the copper-matt nickel powder into the solution, further improving the leaching efficiency. The acidic leaching reaction further dissolves the metal compounds that are not completely dissolved after the alkaline leaching reaction to form soluble metal sulfates, thereby improving the metal recovery rate. Concentrated sulfuric acid is used to lower the pH value and enhance the solution's ability to dissolve residual metals. At the same time, sodium chlorate is added to maintain oxidation conditions to help more metal ions enter the solution state. The temperature, pH value and reaction time are controlled to optimize the leaching conditions to ensure that the copper, nickel and iron metal elements can be effectively transferred to the liquid phase without precipitation, and that precious metals such as gold and platinum are not dissolved but remain in the leaching residue for enrichment. The main chemical reactions involved in the first-stage soda ash and sulfuric acid double leaching reaction are as follows (taking copper as an example, nickel and iron are similar): Alkali leaching reaction: Cu2S+2NaClO3+4NaOH→2Cu(OH)2+2Na2SO4+Na2S; Acid leaching reaction: Cu(OH)2+2H2SO4→CuSO4+2H2O; Na2S+H2SO4→Na2SO4+H2S; Cu2S+2NaClO3+4H2SO4→2CuSO4+2Na2SO4+H2S+2H2O; After the first stage of soda ash and sulfuric acid double leaching reaction is completed and filtered, a first stage of leaching liquid and a first stage of leaching residue are obtained. The first stage of leaching residue is subjected to a second stage of sulfuric acid leaching reaction. The second stage of sulfuric acid leaching reaction is to place the first stage of leaching residue in a 5% sodium chlorate solution and stir evenly, slowly add concentrated sulfuric acid, acid leaching reaction for 90 minutes, control the temperature at 70°C, control the pH at 1.5-2.0, and add sodium chlorate during the period. The chemical reaction of this process is similar to the first stage of acid leaching reaction, which is to acid leaching the first stage of leaching residue again to ensure that more copper, nickel, and iron metals are leached, further improving the leaching rate. After the second stage of sulfuric acid leaching reaction is completed and filtered, a second stage of leaching liquid and a second stage of leaching residue are obtained. The second stage of leaching liquid can be added to the leaching solution for repeated recycling, which improves the utilization rate of the leaching solution and reduces the cost. The second-stage leaching residue is subjected to a three-stage sulfuric acid leaching reaction. The three-stage sulfuric acid leaching reaction is to place the second-stage leaching residue in a 5% sodium chlorate solution and stir it evenly, slowly add concentrated sulfuric acid, and acid leaching for 90 minutes, control the temperature at 70°C, and control the pH at 1.5-2.0. Sodium chlorate is added during this period. The chemical reaction of this process is similar to the first-stage acid leaching reaction. It is to acid leaching the second-stage leaching residue again to further extract the residual copper, nickel, and iron metals to maximize the utilization of metal resources. After the three-stage sulfuric acid leaching reaction is completed and filtered, a three-stage leaching liquid and a three-stage leaching residue rich in precious metals of gold, silver, and platinum are obtained. The three-stage leaching liquid can be added to the second-stage sulfuric acid leaching reaction to improve the utilization rate of the leaching liquid, reduce costs, and reduce the discharge of waste.
[0023] Through this step, copper, nickel and iron metals can be effectively and selectively leached from the copper-matt nickel powder, and these metals can be dissolved in the first-stage leaching solution in the form of soluble salts, preparing for the subsequent recovery of copper, nickel and iron. The third-stage leaching slag is rich in gold, silver and platinum precious metals and can be further processed and sold.
[0024] S4, copper replacement: detect the copper, nickel and iron content in the first leaching solution in step S3 (copper 40g / L, nickel 20g / L, iron 15g / L), add the replacement agent in the first leaching solution according to the mass ratio of replacement agent: copper = 1:1.3 to carry out replacement reaction for 20-30 minutes. The replacement agent is iron powder, and the temperature is controlled at 40-50°C. Iron replaces copper ions (Cu 2+ ) is reduced to copper metal (Cu), while the iron itself is oxidized to divalent iron ions (Fe 2+ ), by controlling the reaction conditions and the amount of iron powder added, the recovery rate and purity of copper can be optimized. After filtration, a copper filter cake and a first filtrate are obtained. The copper filter cake is dried to obtain copper powder (the purity is 92% after testing). The copper powder can be sold. The first filtrate contains nickel, iron and sulfate. The nickel content is 18g / L and the divalent iron content is 90g / L.
[0025] S5, ammonium method for synthesizing ferric phosphate: the first filtrate obtained in step S4 is first heated to 70°C, and hydrogen peroxide and ammonium dihydrogen phosphate are slowly added simultaneously, with the amount of hydrogen peroxide added being 2.4% of the mass of the first filtrate, ensuring that the divalent iron ions (Fe 2+ ) is fully oxidized to ferric iron (Fe 3+ ), which is crucial for the subsequent formation of iron phosphate, because only trivalent iron ions can react with phosphate ions (PO4 3- ) combined to form a stable iron phosphate, the concentration of diammonium phosphate is 45g / L, diammonium phosphate is used as a phosphorus source to provide phosphate ions (PO4 3- ), and add phosphoric acid to control the end point pH 1.6-1.8 to ensure that the reaction is carried out under suitable acidic conditions. After the divalent iron ions are completely converted into trivalent iron ions, the temperature is continued to rise to 95°C, and the phosphate ions (PO4 3- ) ferric ion (Fe 3+ ) combine to form ferric phosphate dihydrate precipitation, the chemical reaction formula is Fe 3+ + NH4H2PO4 + H2O→ FePO4·2H2O + NH 4+ + H + , keep warm for 2-3 hours, age for 3-4 hours to fully precipitate the iron phosphate, obtain dihydrate iron phosphate slurry, filter and separate to obtain iron phosphate filter cake and the second filtrate, the iron phosphate filter cake is washed (conductivity at the washing end point ≤ 500μS / cm), dried at 150℃ for 3 hours, and calcined at 680℃ for 4 hours to obtain battery-grade iron phosphate (iron-phosphorus ratio detected to be 0.976), the second filtrate contains nickel, sulfate, phosphate, and ammonium, and the nickel content is 15g / L.
[0026] S6, sulfidation nickel precipitation: sodium sulfide is added to the second filtrate obtained in step S5, the mass ratio of sodium sulfide to nickel content in the second filtrate is 12:1, the sulfidation reaction is carried out for 30 minutes, the temperature is controlled at 50°C, and the chemical reaction formula is Na2S+Ni 2+ →NiS↓+2Na + , sodium sulfide (Na2S) as a precipitant, and nickel ions (Ni 2+ ) reacts to generate nickel sulfide (NiS). Nickel sulfide is insoluble in water and is therefore separated from the solution in the form of a precipitate. After filtration, a nickel sulfide filter cake and a third filtrate are obtained. The nickel sulfide filter cake is dried to obtain nickel sulfide, which can be sold. The third filtrate (containing ammonia, phosphate, and sulfate) is used to regenerate diammonium phosphate.
[0027] S7, regeneration of ammonium dihydrogen phosphate: add calcium dihydrogen phosphate at 14 g / L to the third filtrate obtained in step S5, control the temperature at 60°C, regenerate for 30-40 minutes, then add ammonia water to adjust the pH to 4.5-5.0, and continue to react for 50-60 minutes. The chemical reaction formula is Ca(H2PO4)2+2NH3⋅H2O+SO4 2- →2NH4H2PO4+CaSO4↓, calcium sulfate will be precipitated in the form of gypsum slag, and calcium sulfate gypsum slag and ammonium dihydrogen phosphate liquid will be obtained after filtration. The ammonium dihydrogen phosphate will be finely filtered again and then recycled to step S5 to synthesize iron phosphate, thereby realizing the recycling of ammonium phosphate. The calcium sulfate gypsum slag can be used as a building material.
[0028] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for recovering copper matte nickel material to prepare copper powder, nickel sulfide and iron phosphate, characterized in that: The following steps are involved: S1, roasting: after uniformly mixing the copper matte nickel material and soda ash in a mass percentage of 1:0.03-0.05, place in a roasting equipment and roast at 800-850° C. for 1.5-3 hours to obtain a roasted material; S2, crushing: placing the calcined material obtained in step 1 in a grinding device and crushing it to 80-120 mesh to obtain copper matte nickel powder; S3, three-stage leaching: the copper matte nickel powder obtained in step S2 is added to the leaching solution at a solid-liquid ratio of 1:5-6, and a first-stage soda ash and sulfuric acid double leaching reaction is carried out. The leaching solution is a mixed solution of sodium chlorate and soda ash, the mass percentage of the sodium chlorate to the copper matte nickel material is 1:32-35, and the soda ash concentration is 10-12g / L. After the first-stage soda ash and sulfuric acid double leaching reaction is completed, a first-stage leaching solution and a first-stage leaching residue are obtained after filtration. The first-stage leaching residue is subjected to a second-stage sulfuric acid leaching reaction, and a second-stage leaching solution and a second-stage leaching residue are obtained after filtration. The second-stage leaching solution can be added to the leaching solution for repeated recycling. The second-stage leaching residue is subjected to a third-stage sulfuric acid leaching reaction, and a third-stage leaching solution and a third-stage leaching residue rich in precious metals of gold, silver, platinum are obtained after filtration. The third-stage leaching solution can be added to the second-stage sulfuric acid leaching reaction; S4, copper replacement precipitation: detect the content of copper, nickel and iron in the first leaching solution in step S3, add a replacement agent to the first leaching solution according to the mass ratio of replacement agent: copper = 1.2-1.4 to carry out replacement reaction for 20-30 minutes, control the temperature at 40-50°C, obtain a copper filter cake and a first filtrate after filtering, and obtain copper powder after the copper filter cake is dried; S5, ammonium method synthesis of iron phosphate: the first filtrate obtained in step S4 is first heated to 70-80°C, and hydrogen peroxide and ammonium dihydrogen phosphate are slowly added simultaneously, wherein the amount of hydrogen peroxide added is 2.1-2.5% of the mass of the first filtrate, and the concentration of ammonium dihydrogen phosphate is 40-45g / L, and phosphoric acid is added to control the end point pH of 1.6-1.
8. After detecting that the divalent iron ions are completely converted into trivalent iron ions, the temperature is further raised to 90-95°C, kept warm for 2-3 hours, aged for 3-4 hours, and dihydrate iron phosphate slurry is obtained. After filtering and separation, an iron phosphate filter cake and a second filtrate are obtained. The iron phosphate filter cake is washed, dried at 140-160°C for 2-3 hours, and calcined at 650-700°C for 3-4 hours to obtain battery-grade iron phosphate; S6, sulfidation and nickel precipitation: sodium sulfide is added to the second filtrate obtained in step S5, the mass ratio of sodium sulfide to nickel content in the second filtrate is 11-13:1, the sulfidation reaction is carried out for 30-40 minutes, the temperature is controlled at 40-50°C, and a nickel sulfide filter cake and a third filtrate are obtained after filtration, and the nickel sulfide filter cake is dried to obtain nickel sulfide; S7, regeneration of diammonium phosphate: add calcium dihydrogen phosphate at 12-15 g / L to the third filtrate obtained in step S5, control the temperature at 55-65° C., regenerate for 30-40 minutes, then add ammonia water to adjust the pH value to 4.5-5.0, and continue to react for 50-60 minutes, and obtain calcium sulfate gypsum slag and diammonium phosphate liquid after filtration. The diammonium phosphate is finely filtered again and then reused in step S5 to synthesize iron phosphate.
2. The method according to claim 1, characterized in that The copper matte nickel material in step S1 includes but is not limited to the following chemical elements: copper, nickel, iron, sulfur, silver, and platinum. The mass percentage of the copper matte nickel material to soda ash is 1:0.
04. The roasting equipment adopts a muffle furnace, and the roasting time is 2 hours.
3. The method according to claim 1, characterized in that The grinding equipment in step S2 is a ball mill, and the crushed particle size of the roasted material is 100 meshes.
4. The method according to claim 1, characterized in that: The mass percentage of sodium chlorate and copper-matt nickel material in the leaching solution of step S3 is 1: 33, the concentration of soda ash is 12g / L, the solid-liquid ratio of copper matte nickel powder to leaching solution is 1:5, the first stage soda ash and sulfuric acid double leaching reaction is to place the copper matte nickel powder in the leaching solution and stir evenly, control the temperature to 70℃-75℃ for alkaline leaching reaction for 30 minutes, then slowly add concentrated sulfuric acid, add sodium chlorate in an amount equal to that of alkaline leaching to continue acid leaching reaction for 60 minutes, and control the pH to 1.5-2.0, the second stage sulfuric acid leaching reaction is to place the first stage leaching residue in 5% sodium chlorate solution and stir evenly, slowly add concentrated sulfuric acid, acid leaching reaction for 90 minutes, control the temperature to 70℃, control the pH to 1.5-2.0, and add sodium chlorate during the period, the third stage sulfuric acid leaching reaction is to place the second stage leaching residue in 5% sodium chlorate solution and stir evenly, slowly add concentrated sulfuric acid, acid leaching reaction for 90 minutes, control the temperature to 70℃, control the pH to 1.5-2.0, and add sodium chlorate during the period.
5. The method according to claim 1, characterized in that In step S4, the mass ratio of the displacing agent to copper is 1:1.3, and the displacing agent is iron powder.
6. The method according to claim 1, characterized in that In step S5, the amount of hydrogen peroxide added is 2.4% of the mass of the first filtrate, and the concentration of ammonium dihydrogen phosphate is 45 g / L.
7. The method according to claim 1, characterized in that The mass ratio of the sodium sulfide in step S6 to the nickel content in the second filtrate is 12:
1.
8. The method according to claim 1, characterized in that In step S7, calcium dihydrogen phosphate is added to the third filtrate at 14 g / L.